The Oil Price Shocks and the Monetary Stability in Saudi Arabia - Alzyadat, Jumah Ahmad (International Journal of Energy Economics and Policy, 2024)
The exposure of major oil exporters to severe shocks in oil prices makes it a strategic factor in determining economic policies, including monetary policy. This paper discusses the interaction of oil price shocks and monetary stability variables in Saudi Arabia. The study used vector autoregression (VAR) techniques. The results from the analysis of impulse response functions and variance analysis indicate that oil price shocks play a major role in fluctuations in the money supply and inflation, The results showed that oil prices are the second most influential factor on the price level after money supply during the response period as well as an important role in the stability of the exchange rate in the Saudi economy. Oil price shocks have a negative impact on exchange rates. In analyzing the components of exchange rate variation, the oil price shock did not play an important role in explaining the exchange rate variation. This suggests that the price of oil is not the most important factor in explaining changes in exchange rates. The price level and money supply are the two factors that most influence the value of the local currency. Therefore, the study suggests that monetary stability can be achieved in Saudi Arabia through a monetary policy capable of controlling liquidity, stabilizing the exchange rate, preserving the purchasing power of the local currency, and combating inflationary pressures, taking into account changes in oil prices.